Kobberrullen (3Q15) fra Qumran i dens litterære sammenhæng - Høgenhaven, Jesper (Dansk Teologisk Tidsskrift, 2016)
The Copper Scroll from Qumran Cave 3 (3Q15) can be meaningfully read as a literary text within the context of ancient Jewish writings generally and of the Qumran library in particular. In 3Q15 a communicative situation is envisaged, with an authoritative voice giving instructions to an addressee, who is imagined as moving around from place to place to retrieve the hidden valuables at various locations. Many of the geographical and personal names mentioned derive their significance from their function in older literary traditions. The state of the Promised Land as described in 3Q15 is one of impurity and desolation, awaiting eschatological redemption. The impression of a desolate ruined landscape is corroborated by references to hiding-places that are regularly presented as deserted ruins, abandoned water installations, and tombs. The treasures described in 3Q15 belong to Solomon’s temple; and the text should be read against the background of the welldocumented legends about those treasures.